Answer:
3
Option D is the correct option.
Explanation:
6 ( 2x - 3 ) = - ( X - 9 ) + 4x
Distribute 6 through the parantheses
12x - 18 = - ( X - 9) + 4x
When there is a (-) in front of an expression in parantheses, change the sign of each term in the expression
12x - 18 = -x + 9 + 4x
Collect like terms
12x - 18 = 3x + 9
Move variable to Left hand side and change its sign
12x - 3x - 18 = 9
Move constant to Right hand side and change its sign
12x - 3x = 9 + 18
collect like term
9x = 9 + 18
Add the numbers
9x = 27
Divide both sides of the equation by 9
9x /9 = 27/ 9
Calculate
X = 3
Hope this helps....
Good luck on your assignment...